Isolation and identification of bacteria in the process of making dry and wet gaplek - Leonardus Patrick Harsono; Masdiana Chendrakasih Padaga; Oki Krisbianto; Erica Cresentia Kurniawan (Agroindustrial Technology, University of Trunojoyo Madura, 2026)
Gaplek is a staple food widely consumed in tropical regions of developing countries. As a source of carbohydrate food, cassava can be processed through industrial development with the dehydration process, with the product being Gaplek. Despite its importance, research on the microorganisms and bacteria involved in the gaplek production process remains limited. This study aims to analyze microorganisms' total plate and yeast mold counts and identify the bacteria involved in dry and wet gaplek production. The research involved enumeration, isolation, and identification stages. Enumeration assessed total plate and yeast mold counts on various media, followed by bacterial identification on PCA media. The results showed that dried gaplek (GD) had the highest plate count on PCA media, with the highest yeast mold count observed in the 0-hour soaked sample (GS0) on PDA media. Enumeration revealed total microorganism, lactic acid bacteria, and yeast mold counts in dried gaplek to be 4.5 x 108, 1.0 x 105, and 2.2 x 108 cfu/gram, respectively. In contrast, for wet gaplek, counts were 3.2 x 108, 2.5 x 108, and 7.1 x 108 cfu/gram, respectively. Bacterial identification involved Gram staining, catalase testing, and biochemical assays, revealing Staphylococcus, Serratia marcescens, and Leuconostoc mesenteroides as potential contributors to dried gaplek production. In contrast, Staphylococcus, Leuconostoc mesenteroides, and Pediococcus pentosaceus were implicated in wet gaplek production.